Засади економічного оцінювання бізнес-проектів у цифровому бізнесі в умовах євроінтеграції - Будинський, Р. З.; Прокопенко, І. В.; Поріцька, А. І.; Budynskyi, R.; Prokopenko, I.; Poritska, A. (Видавництво Львівської політехніки, 2020)
У статті розглянуто визначальні засади економічного оцінювання бізнес-проектів підприємств у цифровому бізнесі в умовах євроінтеграції. Встановлено, що для такого економічного оцінювання можна застосовувати перш за все т. зв. “традиційні” підходи, які описані у літературі з проектного менеджменту, інвестування, управління інноваційними процесами тощо. Розглянуто й інші практичні підходи у цьому контексті, зокрема, Rapid Economic Justification, Total Economic Impact, Total Value of Opportunities, Applied Information Economics, Cost/Schedule Control Systems Criteria, Activity Based Costing, IT Scorecard, Total Cost of Ownership тощо.

The realities of domestic companies’ activities necessitate a more thorough approach not only to the processes of business project management in the digital business in the conditions of European integration, but also to the economic justification of the relevant project solutions. Reasonability and necessity to use a variety of methodological tools for such economic substantiation can be different. For example, there may be a need to choose alternative options of business projects, implementation of new business projects, reengineering or minor improvement of existing business projects and the like. The article deals with the determinants of economic assessment of business projects of enterprises in the digital business in the conditions of European integration. The conclusion is made that this problem is often complicated by the existence of various stakeholders (e. g., heads of institutional level, project team, owners, investors, etc.), who pursue their own interests in relation to a particular business project. These objectives may often be radically different from those of other stakeholders or groups. The literature on project management, investment, innovation management, etc. describes traditional approaches to the economic evaluation of business projects. (for example, traditional financial tools, probability methods, qualitative and financial models, as well as their combination, portfolio analysis, qualitative diagnostics tools, budget method, etc.) . Other practical approaches to economic assessment of business projects of enterprises in the digital business in the conditions of European integration are also considered. In particular, such approaches are Rapid Economic Justification (a method of rapid economic justification of a project solution), Total Economic Impact (establishing the overall economic effect), Total Value of Opportunities (determining the overall value of opportunities), Applied Information Economics (accounting of applied information economy), Cost / Schedule Control Systems Criteria (identification of cost and time indicators C/SCSC), Activity Based Costing (performance of functional cost analysis), IT Scorecard (use of a modified balanced system of indicators), Total Cost of Ownership (calculation of total cost of ownership). The prospects for further research on the problem should consist in the formation of conditions and limitations for the use of different approaches to the economic evaluation of business projects of enterprises in the digital business in the conditions of European integration.
Basics of economic assessment of business projects in digital business in the conditions of european integration
Keywords: бізнес-проект; ефективність; євроінтеграція; інструментарій; оцінювання; цифровий бізнес; business project; efficiency; European integration; tools; evaluation; digital business; 338.4; [658; 005.8]